Experimental and theoretical investigation of anaerobic fluidized bed biofilm reactors - Fuentes,M. (2009)
This work presents an experimental and theoretical investigation of anaerobic fluidized bed reactors (AFBRs). The bioreactors are modeled as dynamic three-phase systems. Biochemical transformations are assumed to occur only in the fluidized bed zone. The biofilm process model is coupled to the system hydrodynamic model through the biofilm detachment rate; which is assumed to be a first-order function of the energy dissipation parameter and a second order function of biofilm thickness. Non-active biomass is considered to be particulate material subject to hydrolysis. The model includes the anaerobic conversion for complex substrate degradation and kinetic parameters selected from the literature. The experimental set-up consisted of two mesophilic (36±1ºC) lab-scale AFBRs (R1 and R2) loaded with sand as inert support for biofilm development. The reactor start-up policy was based on gradual increments in the organic loading rate (OLR), over a four month period. Step-type disturbances were applied on the inlet (glucose and acetic acid) substrate concentration (chemical oxygen demand (COD) from 0.85 to 2.66 g L-1) and on the feed flow rate (from 3.2 up to 6.0 L d-1) considering the maximum efficiency as the reactor loading rate switching. The predicted and measured responses of the total and soluble COD, volatile fatty acid (VFA) concentrations, biogas production rate and pH were investigated. Regarding hydrodynamic and fluidization aspects, variations of the bed expansion due to disturbances in the inlet flow rate and the biofilm growth were measured. As rate coefficients for the biofilm detachment model, empirical values of 3.73⋅10(4) and 0.75⋅10(4) s² kg-1 m-1 for R1 and R2, respectively, were estimated.